Power Sector Reforms: Challenges and the Way Forward - Francis, S.J. (SLEA Quarterly Economic Review (SQER), 2024)
Power sector reforms have been undertaken by many developing countries. These reforms have generally led to the development of the power sector in countries where those were implemented. However, progress at physical, economic, and institutional levels has recorded mixed results, particularly in the areas of market structure, private participation, and regulatory framework. The electricity supply industry emerged in 1900-1950s and the electricity sector reforms began ...
Keywords: Sri Lanka; Power sector reform; Ceylon Electricity Board